The Genus Pachyma (Syn. Wolfiporia) Reinstated and Species Clarification of the Cultivated Medicinal Mushroom “Fuling” in China - Wu, Fang; Li, Shou-Jian; Dong, Cai-Hong; Dai, Yu-Cheng; Papp, Viktor (Frontiers in Microbiology, 2020)
The fungus “Fuling” has been used in Chinese traditional medicine for more than two thousand years, and its sclerotia have a wide range of biological activities including antitumour, immunomodulation, anti-inflammation, antioxidation, anti-ageing etc. This prized medicinal mushroom also known as "Hoelen" is resurrected from a piece of pre-Linnean scientific literature. Fries treated it as Pachyma hoelen Fr. and mentioned that it was cultivated on pine trees in China. However, this name had been almost forgotten, and Poria cocos (≡ Wolfiporia cocos), originally described from North America, and known as “Tuckahoe” has been applied to “Fuling” in most publications. Although Merrill mentioned a hundred years ago that Asian Pachyma hoelen and North American P. cocos are similar but different, no comprehensive taxonomical studies have been carried out on the East Asian Pachyma hoelen and its related species. Based on phylogenetic analyses and morphological examination on both the sclerotia and the basidiocarps which are very seldomly developed, the East Asian samples of Pachyma hoelen including sclerotia, commercial strains for cultivation and fruiting bodies, nested in a strongly supported, homogeneous lineage which clearly separated from the lineages of North American Wolfiporia cocos and other species. So we confirm that the widely cultivated “Fuling” Pachyma hoelen in East Asia is not conspecific with the North American Wolfiporia cocos. Based on the changes in Art. 59 of the International Code of Nomenclature for algae, fungi, and plants, the generic name Pachyma, which was sanctioned by Fries, has nomenclatural priority (ICN, Art. 13.1), and this name well represents the economically important stage of the generic type. So we propose to use Pachyma rather than Wolfiporia, and subsequently Pachyma hoelen and Pachyma cocos are the valid names for “Fuling” in East Asia and “Tuckahoe” in North America, respectively. In addition, a new combination, Pachyma pseudococos, is proposed. Furthermore it seems that Pachyma cocos is a species complex, and that three species exist in North America.